Effectiveness of ERP-Based Accounting Information System Implementation in Improving Operational Efficiency of Manufacturing Companies - Rizqiyatul Khoiriyah; Aan Jelli Priana (Dhana, 2025)
This study aims to analyze the effectiveness of Enterprise Resource Planning (ERP)-based accounting information system implementation in improving operational efficiency in manufacturing companies. The background of this research is based on the company's need to integrate business processes digitally, as well as the lack of empirical studies that directly measure the impact of ERP implementation on work efficiency. The method used is a quantitative approach through a survey of 46 respondents from four manufacturing companies. Data was collected using a questionnaire measuring five dimensions of ERP implementation: module integration, user training, ease of access, system reliability, and management support. The results showed that ERP implementation was in the high category (mean score 4.12) and had a positive impact on operational efficiency (mean score 4.08). Pearson correlation test showed a significant positive relationship between the level of ERP implementation and operational efficiency (r = 0.648, p < 0.001), while simple linear regression test showed that ERP contributed to 42% of the variation in operational efficiency (R² = 0.420). Nonetheless, non-technical barriers such as resistance to change, digital literacy gaps, and lack of advanced training were also found. The findings confirm that successful ERP implementation does not only depend on technological readiness, but also requires managerial support and overall organizational readiness.